PELAPISAN PERMUKAAN DALAM NOSEL ROKET RKX100 DENGAN Cr2C3-NiCr HVOF: OPTIMASI KEKUATAN LEKAT MELALUI VARIASI KEKASARAN PERMUKAAN - Sofyan, Bondan T. Sofyan; Prasetyo, Yus; Ardiansyah, Sayid; Sofyan, Edy (BRIN Publishing, 2004)
Nozzle of RKX100 rocket contributes 30 percent to the total weight of the structure, so that allowing further research on weight reduction. An alternative for this is by substitution of massive graphite, which is currently used as thermal protector in the nozzle, with thin layer of HVOF (High Velocity Oxy-Fuel) thermal spray layer. A series of study on the characteristics of various type of HVOF coating material have been being conducted. This paper presented the investigation on the HVOF Cr2C3-NiCr thermal spray coating, in particular, the optimization of bonding strength by varying surface roughness of substrates. Characterization included bonding strength test, micro hardness measurement and micro structural observation with optical microscope and scanning electron micriscope (SEM). The results showed that grit blasting pressure increass the surface roughness from 4,54 um to 5.72 um at the pressure of 6 bar. Average micro hardness of the coating was 631 VHN 300. Coating applied to the surface with rougness of 5.42 um possessed the highest bonding strength, 44 MPa. Microstructural observation by using optical microscope and scanning electron microscope (SEM) confirmed dense lamellae structure with variable composition. High coating adherence was found to be due to mechanical interlocking.